Differentiation of Brain Pericyte‐Like Cells from Human Pluripotent Stem Cell−Derived Neural Crest. Issue 1 (20th January 2021) - Gastfriend, Benjamin D.; Stebbins, Matthew J.; Du, Feifan; Shusta, Eric V.; Palecek, Sean P.
Abstract: Brain pericytes regulate diverse aspects of neurovascular development and function, including blood‐brain barrier (BBB) induction and maintenance. Primary brain pericytes have been widely employed in coculture‐based in vitro models of the BBB, and a method to generate brain pericytes from human pluripotent stem cells (hPSCs) could provide a renewable, genetically tractable source of cells for BBB modeling and studying pericyte roles in development and disease. Here, we describe a protocol to differentiate hPSCs to NG2 + PDGFRβ + αSMA low brain pericyte‐like cells in 22‐25 days through a p75‐NGFR + HNK‐1 + neural crest intermediate, which mimics the developmental origin of forebrain pericytes. The resulting brain pericyte‐like cells have molecular and functional attributes of brain pericytes. We also provide protocols for maintenance, cryopreservation, and recovery of the neural crest intermediate, and for molecular and functional characterization of the resulting cells. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Differentiation of hPSCs to neural crest Basic Protocol 2 : Differentiation of neural crest to brain pericyte‐like cells Support Protocol 1 : Flow cytometry analysis of neural crest cells Support Protocol 2 : Maintenance, cryopreservation, and recovery of neural crest cells Support Protocol 3 : Molecular characterization of brain pericyte‐like cells Support Protocol 4 : Cord formation assay with endothelial cells and brain pericyte‐like cells